SEDENTARY PHYSICAL ACTIVITY WITH BODY MASS INDEX AMONG PRECLINICAL STUDENTS AT THE FACULTY OF MEDICINE OF WIDYA MANDALA CATHOLIC UNIVERSITY OF SURABAYA - Destino Huvi; Dewa Ayu Liona Dewi; Tabita Novita Anggriani (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: The percentage of individuals with a body mass index (BMI) above normal continues to increase every year. Sedentary physical activity is one of the factors that may cause an increase in BMI. IMT is a statistical indicator that applies an individual's weight and height to determine weight categories at all age groups. Sedentary physical activity refers to an activity in a conscious state that only expends energy of ≤1.5 Metabolic Equivalent of Task (MET).Objective: To determine the correlation between sedentary physical activity and BMI among preclinical students at the Faculty of Medicine, Widya Mandala Catholic University of Surabaya.Methods: This was an observational analytical study with cross-sectional design. The samples were selected through simple random sampling. The data source for this study were derived from primary data in the form of interviews using the International Physical Activity Questionnaire (IPAQ) and direct measurement towards 159 students.Results: 41.5%  of students had normal BMI and 33.3% of students had sedentary physical activities. Based on the results of Spearman correlation test, it was found that there was a strong and significant relationship between sedentary physical activity and body mass index (p value=0.000 with r=0.641).Conclusions: There was a significant positive correlation between sedentary physical activity and BMI, which indicated that the higher the sedentary physical activity, the higher the BMI. Such relationship suggested that sedentary physical activity had a positive role in the incidence of overweight and obesity.